2006
DOI: 10.1002/adfm.200500420
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport and Photocurrent Generation in Poly(3-hexylthiophene): Methanofullerene Bulk-Heterojunction Solar Cells

Abstract: The effect of controlled thermal annealing on charge transport and photogeneration in bulk‐heterojunction solar cells made from blend films of regioregular poly(3‐hexylthiophene) (P3HT) and methanofullerene (PCBM) has been studied. With respect to the charge transport, it is demonstrated that the electron mobility dominates the transport of the cell, varying from 10–8 m2 V–1 s–1 in as‐cast devices to ≈3 × 10–7 m2 V–1 s–1 after thermal annealing. The hole mobility in the P3HT phase of the blend is dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
1,174
6
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,260 publications
(1,269 citation statements)
references
References 31 publications
81
1,174
6
8
Order By: Relevance
“…Whilst space charge build up due to low hole mobility limits the photocurrent in non-annealed devices, increased hole mobility 8 and resulting balance in charge mobilities upon annealing eliminate this problem in annealed devices. 53 However, the effect of annealing on transport is variable and the annealed and non-annealed devices can show comparable values for the majority carrier mobility-lifetime product. The efficiency gain upon annealing is therefore more commonly attributed to reduced recombination losses, resulting from the increased phase segregation and molecular ordering, and increased spectral photocurrent generation in the near-IR than to improved transport.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…Whilst space charge build up due to low hole mobility limits the photocurrent in non-annealed devices, increased hole mobility 8 and resulting balance in charge mobilities upon annealing eliminate this problem in annealed devices. 53 However, the effect of annealing on transport is variable and the annealed and non-annealed devices can show comparable values for the majority carrier mobility-lifetime product. The efficiency gain upon annealing is therefore more commonly attributed to reduced recombination losses, resulting from the increased phase segregation and molecular ordering, and increased spectral photocurrent generation in the near-IR than to improved transport.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…[89][90][91][92] In macroscopic modeling, the electron and hole mobilities are usually fitted from the space-charge-limited current regime of the single-carrier devices, while the geminate recombination (GR) rate is used as a fitting…”
Section: Braun-onsager Modelmentioning
confidence: 99%
“…6(d)]. 40 Loos and coworkers studied the morphology of spin cast and postannealed P3HT:PCBM blends. 41 In their studies, it was shown that for the spincoated films, P3HT formed interconnecting fibrillar crystals and in a matrix of homogeneously mixed P3HT and PCBM.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%